A Review of Integrated Urban Planning Tools for Greenhouse Gas Mitigation : Linking Land Use, Infrastructure Transition, Technology, and Behavioral Change - Global Platform for Sustainable Cities (World Bank, Washington, DC, 2020)
Achieving the Sustainable Development Goals (SDGs) over the next 30 years will critically depend upon urban land use and infrastructure development actions taken across multiple sectors (buildings, energy, transportation, water-sanitation, and waste) in global cities. Integrated urban planning addresses a multiplicity of urban sustainability objectives (e.g., economy, environment, inclusivity, and resilience) (GPSC, World Bank 2018), including cross-sectoral and cross-scale linkages (Ramaswami et al. 2016) and connection of physical planning with social, cultural, behavior, and policy dimensions. The objective of this report is to review the state of knowledge (science) and the state of practice (models actually used by cities for policy) for modeling the GHG mitigation benefits achievable through integrated urban planning across the four levers, with attention to the foundational Lever 1, CUD. Although the field of urban sustainability is relatively young, and the availability of robust data is uneven across world cities, our review found that significant scientific advances have occurred in modeling the four levers representing integrated urban planning in the context of GHG mitigation. Within each of the four levers, more than 30+ strategies were identified in the literature. For all the strategies, the GHG mitigation potential can be modeled using the same structure of algorithms, which is computed by multiplying two key parameters: the first parameter is the strategy effect per unit of an intervention, i.e., the reduction in demand or resource use per unit of intervention. The second parameter is the penetration rate or adoption rate of each intervention in the strategy scenario. Examples include the percentage of households experiencing CUD improvements or purchasing energy-efficient cars compared to the baseline. This rate has a high impact on the citywide potential for GHG mitigation from implementing a strategy and is shaped by human behavior and policy.